Operational control on environmental safety of potentially toxic elements during thermal conversion of metal-accumulator invasive ragweed to biochar. (10th September 2018) - Yousaf, Balal; Liu, Guijian; Abbas, Qumber; Ali, Muhammad Ubaid; Wang, Ruwei; Ahmed, Rafay; Wang, Chengming; Al-Wabel, Mohammad I.; Usman, Adel R.A.
Abstract: Ragweed (Ambrosia artemisiifolia L.), a metal-accumulator invasive species, was pyrolyzed under a range of pyrolytic conditions to investigate their influence on immobilization and environmental safety of potentially toxic elements (PTEs) in the produced biochar. Conditions tested included temperature, retention time, heating rate, gas flow rate and particle size. Temperature and particle size had pronounced effects on product yields and physico-chemical characteristics of the produced biochar. All PTEs were enriched in the biochar, and the effect was more pronounced with higher temperature over 500 °C. However, fractionation of PTEs in biochar by following the sequential extraction process indicates that the mobile (bioavailable) fraction of most of the PTEs was transformed into more stabilized (residual) form (P < 0.01) after thermal conversion. Conclusively, biochar from metal-accumulating invasive ragweed with sustainable disposal and desired characteristics (with an optimal temperature range of a 500–600 °C and heating rate of 10 min −1 using smaller-size particle) can be produced by an appropriate combination of different pyrolytic condition with low environmental and ecological risk. Highlights: Transformation of metal-accumulator invasive species into value-added products. Temperature and particle size were the most influential factors affecting PTEs. Available fractions of PTEs in biochars were prominently reduced with pyrolysis. PTEs were converted into more stabilized fraction after thermal conversion. Biochars produced under all operating conditions poses a low ecological risk.